Evaluation of Seismic Effects on Atmospheric Pressure Liquid Storage Tanks - Luca Chiappelloni; Francesco Serraino; Valerio Belardi; Simone Trupiano; Luca Gaetani; Francesco Vivio (Engineering Proceedings, 2025)
As part of the seismic capacity assessment of thin-walled tanks containing liquid fuels, the appropriate modeling of hydrodynamic loads is required. The theory adopted in existing work requires the modeling of the hydrodynamic pressure contribution due to tank deformability, which, however, cannot be calculated in closed form. The approach adopted in this work uses acoustic–structural modal analysis to obtain the deformation and response period required to calculate this contribution. The use of the proposed method, on a finite element model, allows the implementation of thickness variability and more geometric detail in the modal analysis. On the other hand, using the obtained load distributions, in non-linear static analyses, reduces the computational time compared to dynamic simulations. In addition, analyses can be performed by importing a pre-deformed surface derived from a three-dimensional scan of the real tank into the final model, thus including the effect of geometric imperfections. As a case study, an existing tank model was produced and analyzed, and the same damage patterns documented in real cases following seismic events were obtained. Therefore, due to the low computational cost, this method is appropriate to be reproduced for a statistically significant number of load cases.